2009
DOI: 10.1159/000236149
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcome of Pregnancies with Parvovirus B19 Infection over Seven Years in a Tertiary Fetal Medicine Unit

Abstract: Objectives: To determine rates of fetal anaemia and pregnancy outcome in susceptible pregnant women infected with human parvovirus B19 infection in a tertiary fetal medicine department over a 7-year period. Additional features enabling identification of fetuses that progress to severe anaemia were also investigated. Methods: Forty-seven susceptible, pregnant women with confirmed parvovirus infection referred to a regional fetal medicine unit, over a 7-year period (1999–2006), were identified. Where possible ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 30 publications
0
35
0
3
Order By: Relevance
“…Most cases are detected upon the fi nding of fetal hydrops in the ultrasound assessment, although there are also pregnant women referred due to seroconversion for parvovirus B19. Close ultrasonographic surveillance on a weekly basis for 10 -12 weeks after the estimated time of exposure for signs of fetal anemia, heart failure, and hydrops and Doppler screening (Doppler examination of the MCA) after initial seroconversion can identify the subgroup with fetal anemia that needs to be transfused [71] . Delle Chiaie et al observed that a cut-off value of 1.29 MoM for MCA-PSV could predict any degree of fetal anemia induced by parvovirus infection with sensitivity and specifi city of 100 % [17] .…”
Section: Iut In Other Diseasesmentioning
confidence: 99%
“…Most cases are detected upon the fi nding of fetal hydrops in the ultrasound assessment, although there are also pregnant women referred due to seroconversion for parvovirus B19. Close ultrasonographic surveillance on a weekly basis for 10 -12 weeks after the estimated time of exposure for signs of fetal anemia, heart failure, and hydrops and Doppler screening (Doppler examination of the MCA) after initial seroconversion can identify the subgroup with fetal anemia that needs to be transfused [71] . Delle Chiaie et al observed that a cut-off value of 1.29 MoM for MCA-PSV could predict any degree of fetal anemia induced by parvovirus infection with sensitivity and specifi city of 100 % [17] .…”
Section: Iut In Other Diseasesmentioning
confidence: 99%
“…In a recent review [8], perinatal survival after IUT was 66.7-72.2% in parvovirus B19-infected fetuses versus 80.0-93.5% in cases of red blood cell alloimmunization. Other series comprising transfusions in parvovirus B19-induced anemia found survival rates between 33 and 100% (cumulative percentage 78%) [1,6,11,12,[23][24][25][26][27][28][29]. GA varied between studies, but cases before 20 weeks of gestation were rarely included.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to a number of studies reporting the outcome of IUTs in red blood cell alloimmunization [8][9][10], data on intrauterine treatment of parvovirus B19-related anemia are limited [1,6,11,12]. While the majority of transfusions in red blood cell alloimmunization are performed beyond 20 weeks, parvovirus B19 often affects fetuses in the early second trimester.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parvovirus B19 infection called "erythema infectiosum" usually causes a febrile illness but may be a problem especially in patients with chronic hemolytic anemia and pregnant women. 7,8 Transmission is mainly through respiratory droplets but possible by transfusion of infected blood products. 9 In pregnant women the virus passes through placenta.…”
mentioning
confidence: 99%